2017
DOI: 10.1186/s40729-017-0106-2
|View full text |Cite
|
Sign up to set email alerts
|

Porous titanium granules in the treatment of peri-implant osseous defects—a 7-year follow-up study

Abstract: BackgroundA great number of different treatment protocols for peri-implantitis have been suggested but there is no consensus regarding the most effective intervention. The aim of the present study was to evaluate the long-term clinical and radiographic results from a study on peri-implant osseous defect reconstruction.Patients having participated in a randomized clinical study 7 years earlier were invited for a re-examination. The treatment procedures included open flap debridement (OFD) with or without defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 27 publications
1
59
0
Order By: Relevance
“…A low risk of bias was noted in one study only (Isehed et al., ), based on the apparent difficulty to blind the examiner during radiological assessments in the studies evaluating bone replacement grafts (detection bias). In addition, a substantial patient dropout was noted for the long‐term follow‐up (7 years) for two studies (Andersen, Aass, & Wohlfahrt, ; Schwarz et al., ). This, however, was not relevant for outcomes at 12 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A low risk of bias was noted in one study only (Isehed et al., ), based on the apparent difficulty to blind the examiner during radiological assessments in the studies evaluating bone replacement grafts (detection bias). In addition, a substantial patient dropout was noted for the long‐term follow‐up (7 years) for two studies (Andersen, Aass, & Wohlfahrt, ; Schwarz et al., ). This, however, was not relevant for outcomes at 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies with controls reported on changes of CAL, REC or PROMs. Implant survival over at least 5 years was described in one of the interventional studies (Andersen et al., ). Over a 7‐year follow‐up, 3 of 17 implants were lost in three patients, all belonging to the test group (porous titanium granules).…”
Section: Resultsmentioning
confidence: 99%
“…Available data are either based on retrospective assessments (Berglundh, Wennström, & Lindhe, 2018) or on samples of limited size (Andersen, Aass, & Wohlfahrt, 2017; Heitz‐Mayfield et al., 2018; Roccuzzo, Pittoni, Roccuzzo, Charrier, & Dalmasso, 2017; Schwarz, John, Schmucker, Sahm, & Becker, 2017). In these reports, different treatment protocols were evaluated, including open‐flap debridement (Heitz‐Mayfield et al., 2018), pocket elimination/reduction (Berglundh et al., 2018; Serino, Turri, & Lang, 2015), and reconstructive approaches (Andersen et al., 2017; Roccuzzo et al., 2017; Roos‐Jansåker, Persson, Lindahl, & Renvert, 2014; Schwarz et al., 2017). While data from all studies indicated that disease progression could be suppressed in the long‐term, a subgroup of implant sites displayed recurrence/progression of peri‐implantitis after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Information on long-term outcomes following surgical therapy of peri-implantitis is limited. Available data are either based on retrospective assessments (Berglundh, Wennström, & Lindhe, 2018) or on samples of limited size (Andersen, Aass, & Wohlfahrt, 2017;Heitz-Mayfield et al, 2018;Roccuzzo, Pittoni, Roccuzzo, Charrier, & Dalmasso, 2017;Schwarz, John, Schmucker, Sahm, & Becker, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the primary outcome was the radiographic bone filling and although it is true that statistically significant differences were found in favor of the test group, it is necessary to admit the difficulty of distinguishing the biomaterial at the radiographic level. However, other studies describe contradictory results regarding the use of this biomaterial (22,23).…”
Section: Introductionmentioning
confidence: 99%